Comprehensive Physiotherapy Approaches for Children With Cerebral Palsy: Overview and Contemporary Trends - Changho Kim (Korean Research Society of Physical Therapy, 2023)
Cerebral palsy (CP) is a prevalent neurodevelopmental disorder characterized by motor and postural impairments caused by central nervous system dysfunction. It significantly impacts children's daily functioning and quality of life. Physical therapy is a crucial intervention for children with CP that aims to improve motor skills and functional abilities. This study aimed to provide a comprehensive overview of holistic physical therapy approaches methods specifically designed for children with CP and examine recent research trends and their implications for optimizing outcomes in this population. This study employed a narrative review approach, conducting a comprehensive examination of the current literature pertaining to physical therapy methods for children with CP. The review encompassed studies exploring assessment techniques, evidence-based interventions, and innovative approaches in the field. It was discerned that encompassing physical therapy strategies, which encompass individualized treatment plans, evidence-based interventions, and the integration of innovative techniques, yield a favorable influence on the motor skills and functional capacities of children with CP. This review synthesizes the current knowledge on effective physical therapeutic strategies for children with CP. Furthermore, this review highlights the need for continued research and innovation in the field of pediatric physical therapy for CP.